A Multifunctional 3D Supermolecular Co Coordination Polymer With Potential for CO2 Adsorption, Antibacterial Activity, and Selective Sensing of Fe3+/Cr3+ Ions and TNP - Zhou, Xiaojing; Liu, Lili; Kou, Hang; Zheng, Shimei; Song, Mingjun; Lu, Jitao; Tai, Xishi (Frontiers in Chemistry, 2021)
A 3D supermolecular structure [Co3(L)2 (2,2′-bipy)2](DMF)3(H2O)3 1) (H3L = 4,4′,4″-nitrilotribenzoic acid) has been constructed based on H3L, and 2,2′-bipy ligands under solvothermal conditions. Compound 1 can be described as a (3, 6)-connected kgd topology with a Schläfli symbol (43)2(46.66.83) formed by [Co3(CO2)6] secondary building units. The adsorption properties of the activated sample 1a has been studied; the result shows that 1a has a high adsorption ability: the CO2 uptakes were 74 cm3·g−1 at 273 K, 50 cm3·g−1 at 298 K, the isosteric heat of adsorption (Qst) is 25.5 kJ mol−1 at zero loading, and the N2 adsorption at 77 K, 1 bar is 307 cm3 g−1. Magnetic measurements showed the existence of an antiferromagnetic exchange interaction in compound 1, besides compound 1 exhibits effective luminescent performance for Fe3+/Cr3+ and TNP.